Epigenetics, 1-Carbon Metabolism, and Homocysteine During Dysbiosis - Singh, Mahavir; Hardin, Shanna J.; George, Akash K.; Eyob, Wintana; Stanisic, Dragana; Pushpakumar, Sathnur; Tyagi, Suresh C. (Frontiers in Physiology, 2021)
Although high-fat diet (HFD) induces gut dysbiosis and cardiovascular system remodeling, the precise mechanism is unclear. We hypothesize that HFD instigates dysbiosis and cardiac muscle remodeling by inducing matrix metalloproteinases (MMPs) that lead to an increase in white adipose tissue and treatment with lactobacillus (a ketone body donor from lactate; the substrate for the mitochondria) reverses dysbiosis-induced cardiac injury, in part, by increasing lipolysis (PGC-1α, and UCP1), adipose tissue browning and decreasing in lipogenesis. To test this hypothesis, we used wild type (WT) mice fed with HFD for 16 weeks with/without a probiotic (PB) in water. Cardiac injury was measured by CKMB activity which was found to be robust in HFD fed mice. Interestingly, CKMB activity was normalized post PB treatment. Levels of free fatty acids (FFAs), and methylation were increased but butyrate was decreased in HFD mice suggesting epigenetically governed 1-carbon metabolism along with dysbiosis. Levels of PGC-1α, and UCP1 were measured by Western blot analysis, and MMP activity was scored via zymography. Collagen histology was also performed. Contraction of the isolated myocytes was measured employing the ion-optic system, and functions of the heart were estimated by Echocardiography. Our results suggest that mice on HFD gained weight and exhibited an increase in blood pressure. These effects were normalized by PB. Levels of fibrosis, and MMP-2 activity were robust in HFD mice, and treatment with PB mitigated the fibrosis. Myocyte calcium-dependent contraction was disrupted by HFD, and treatment with PB could restore its function. We conclude that HFD induces dysbiosis, and treatment with PB creates eubiosis, and browning of the adipose tissue.